Application and impacts of sustainable development goals in large Brazilian industries - Silva, Luiz Henrique Vieira da; De Benedicto, Samuel Carvalho; Bittencourt, Josias Jacintho; Sugahara, Cibele Roberta; Conti, Diego de Melo (Revista de Administração da UFSM, 2022)
Objective: To verify whether large private companies in the industrial sector operating in Brazil meet the Sustainable Development Goals (SDGs) established by the UN in the 2030 Agenda, in order to provide a return to society on business performance on the agenda of sustainable development. Methods: The research is characterized as qualitative, with exploratory and descriptive purpose, and documentary procedure. Content analysis was chosen as a technique to investigate the collected data. Results: There is a partial compliance of the SDGs by the 20 largest private companies in the industrial sector that have recently published sustainability reports. Conclusions: The report is an important part of sustainability in corporations but presenting it annually does not turn the company into a sustainable organization. Therefore, questions are suggested that can bring companies' actions closer to the dimensions proposed in the 2030 Agenda. It is also recommended to standardize the SDGs as ways to implement sustainable attitudes in companies and, therefore, to build better sustainability reports. This may favor comparative analyses between similar organizations and the implementation of responsible practices capable of responding to the challenges of the 21st century.